Factores laborales y estilos de vida del personal de salud del Puesto de Salud del Huayco. Provincia y Región de San Martín. Agosto – diciembre 2018 - Carhuapoma Herrera, Sandy Julissa (2019)
The objective of this research was to: Determine the relationship that exists between work factors and the lifestyle of the health personnel of Huayco Health Post. Province and Region of San Martín. August - December 2018, the study was non-experimental, quantitative, descriptive, cross-sectional, correlational, the sample consisted of 31 health personnel from the Huayco Health Post, the instrument used was the survey. In the results obtained within the sociodemographic characteristics, it can be shown that the majority of health personnel are between the ages of 31 to 50 years of age (58,06%), are female (70.96%), they profess the catholic religion (77.41%), they are nursing technicians (38.70%), 54.84% (17) present labor factors related to the pressure and demand with a medium level, followed by a 25.81% % (8) low level and 19.35% (6) high level, 67.74% (21) present medium stressful organizational factors, followed by 19.35% (6) low and 12.90% ( 4) high, 67.74% (21) present environmental stressors medium, followed by 16.13% (5) that are high and low simultaneously, 58.06% (18) present healthy lifestyles, followed of unhealthy lifestyles with 29.03% (9) and only 12.90% (4) have very healthy lifestyles. Concluding that: To determine between the labor factors and personal health lifestyles of the Huayco Health Post, the non-parametric chi-square test was applied with a significance level of 95% (p <0.05). The results reflect that there is no significant relationship between both study variables.